Agricultural holdings with undefined boundaries, communal systems and counter‐hegemonies: The persistence of the peasantry in Argentina. (4th May 2020) - Paz, Raúl G.
Abstract: The presence of agricultural holdings with undefined boundaries (AHUBs) and their heterogeneous geographical distribution questions the supposed hegemony of agribusiness in Argentina. Given the lack of defined boundaries, these holdings generate a communal culture among dwellers, which is reflected in both the strategies of the use of commons and the initiatives for the defence of land in the conflicts between peasants and entrepreneurs. This article describes two counter‐enclosure experiences that were generated and have developed on the bedrock of AHUBs and a communal matrix. Those defence strategies are employed by families that possess the land but have not title to it, being a defence tactic against attempts of eviction. AHUB not only is a new census category that allows us to enhance our knowledge of the rural world but also proposes modes of production that differ from those of the capitalist model, showing possible counter‐hegemonic development alternatives that arise from the practices used in these holdings.